PENGARUH KARAKTERISTIK INDIVIDU, KEMAMPUAN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA LPD DESA ADAT TUMBAKBAYUH KECAMATAN MENGWI - Ni Kadek Dewi Lestari; Ni Nyoman Suryani; I Nyoman Mustika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Human Resources (HR) plays a very important role in the company. Human resources are the basic capital in determining company goals. Company goals will be achieved when employees have high performance. This study aims to determine the effect of individual characteristics on employee performance, the effect of work ability on employee performance, the effect of work experience on employee performance at the LPD Desa Adat Tumbakbayuh, Mengwi District. The sample in this study were all employees totaling 34 people. Data analysis using multiple linear regression analysis techniques to answer the problem formulation with the help of the SPSS program. The results of testing the hypothesis show that the variables: 1) Individual characteristics have a positive and significant effect on employee performance 2) Work ability has a positive and significant effect on employee performance 3) Work experience has a positive and significant effect on employee performance